Type 2 diabetes, insulin resistance and effects of exercise in young adults - Burns, Nicole J. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2010)
Study 1- Characteristics of the physically active but insulin resistant phenotype. Methods: Data from the European Group on Insulin Resistance- Relationship between Insulin Sensitivity and Cardiovascular Risk study was used in this analysis. Participants underwent a euglycaemic-hyperinsulinaemic clamp with a continuous insulin infusion rate of 240 pmol-min-1.m-2 and a variable dextrose infusion that was adjusted to maintain a plasma glucose concentration between 4.5-5.5 mmol.1-1. Physical activity was measured over 7 days using an accelerometer. Phenotypic and biochemical differences between subjects in the upper tertile of physical activity and lower tertile of insulin sensitivity (AIR) were compared with those in the lower tertile of physical activity and upper tertile of insulin sensitivity (IIS).
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin